Japan the ultimate samurai guide; an insider looks at the Japanese martial arts and surviving in the land of Bushido and Zen - Benneth, Alexander (North Clarendon, VT Tuttle Publishing, 2018)
This is the first book to provide an accurate insider's view of what the martial arts culture in Japan is really like, and the basic knowledge necessary to explore and learn a martial art successfully there. It provides a complete overview of the subject in a way that is down to earth and accessible. Aimed at people who have an interest in studying Japanese culture, this book presents the reader with relevant and practical information on how to approach various complicated issues they will encounter in Japan. It will be of tremendous help to young martial artists as well as anyone curious about the significance of the Samurai culture phenomenon. The content will also be of use to those engaged in martial arts outside Japan, serving as an invaluable resource for teachers and practitioners alike.
Preface: Budo for the soul -- Chapter 1: Who were the Samurai? -- Chapter 2: Core concepts of Bushido -- Chapter 3: Killing as an art form -- Chapter 4: Martial arts in Japan today -- Chapter 5: Life in a Japanese Dojo -- Chapter 6: Surviving Japan
Keywords: Bushido; Samurai -- Conduct of life; Japan -- Social life and customs; Martial arts -- Japan history; Manners and customs